CONCEPTUAL DEBATE ON ELECTION CRISES IN THE CONTEXT OF DISASTERS - Zulhadi, Zulhadi; Alfirdaus, Laila Kholid; Fitriyah, Fitriyah; Kushandajani, Kushandajani (CosmoGov: Jurnal Ilmu Pemerintahan, 2026)
This study employs a literature review method to analyze post-disaster election crises—often characterized by incumbent victories and shifts in power—through the lenses of leftist and liberal theory. The findings reveal that the leftist approach (Gramsci, Marx, Arendt) highlights the state's vulnerability, while the liberal approach critiques this perspective. This paper proposes the concept of a “third way” that emphasizes social-democratic cohesion to bridge the theoretical divide. This paper finds that the leftist approach—rooted in the thought of Gramsci, Marx, and Arendt—is highly valuable for understanding the relationship between state power and other scholarly studies. The leftist approach views the election crisis not merely as a neutral exercise of state power serving the people’s interests, but as a process that is also vulnerable to resistance against the state. However, this paper acknowledges that the power debate regarding the electoral crisis, as framed through the leftist paradigm, still has weaknesses. The leftist approach has consistently maintained that the state’s role as an oppressor is a weak one. Consequently, various criticisms have emerged from liberals, particularly regarding the understanding of the electoral crisis in the context of natural disasters. Beyond the polar divide between left and right in understanding the concept of the electoral crisis in the context of disasters, there is not only a relationship of class power dynamics but also a strong interdependence between society and democracy. Cohesion is the key concept in understanding the electoral crisis in the context of a disaster by juxtaposing the left and right approaches.